Acute Toxicity and Transgenerational Effects of Perfluorobutane Sulfonate on Caenorhabditis elegans. (25th May 2021) - Chowdhury, Manjurul Islam; Sana, Tanmoy; Panneerselvan, Logeshwaran; Dharmarajan, Rajarathnam; Megharaj, Mallavarapu
Abstract: Perfluorobutane sulfonate (PFBS), due to its increasing use as an alternative to perfluooctane sulfonate (PFOS), is widely detected in humans and the environment, necessitating the evaluation of its potential ecotoxicological risk. We assessed the toxicity and bioaccumulation potential of PFBS in Caenorhabditis elegans, using lethality, locomotion, reproduction, life span, growth, and chemotactic behavior as the effect parameters. In addition, a total of 6 generations of exposed parent animals were monitored for locomotion, brood, and life span behaviors. Life span and brood size were significantly reduced in parent nematodes (P0) following exposure to ≥0.1 mM PFBS, but these negative effects did not transfer to the progeny. Although there was no remarkable effect on reproduction and life span in parent worms exposed to ≤0.01 mM PFBS, multigenerational exposure at 0.0005 mM significantly affected the F4 and F5 progeny. Furthermore, 0.01 to 2.0 mM of PFBS substantially retarded the locomotion behavior of P0 worms. At higher concentrations such as 1.0 mM, this negative effect on locomotion was transferred to the next generation (F1) but later recovered from F2 progeny onward. Our findings demonstrate for the first time that chronic exposure to PFBS at higher concentrations can cause behavioral toxicity and could be transferred to the progeny. These findings have significant implications for the environmental risk assessment of PFBS. Environ Toxicol Chem 2021;40:1971–1980. © 2021 SETAC.